Adam af Bremen og de mundtlige kilder - Lund, Niels (Historisk Tidsskrift, 2018)
Adam of Bremen and his oral sources It has been accepted that Adam of Bremen referred to his sources very meticulously and was faithful to them. In fact, he dealt quite highhandedly with sources that not only posterity but also contemporaries were able to check. This raises the question: how did he deal with oral sources that neither contemporaries nor posterity could check up on? He refers to a Danish bishop and to Sven Estridson, a Danish king, for important information about Danish history. The Danish bishop was probably a German, like all his colleagues but one, and King Sven is purposefully built up to be a great historical authority; praise is lavished on him for his wisdom, his truthfulness and his fantastic memory, and Adam refers to him in many unproblematic contexts to establish him as an authority. Afterwards, Adam cites the king in support of some of his most incredible stories, like his account of the massacre of priests in Oldenburg, the story about the capture of bishop Gerbrand by Unwan, archbishop of Bremen, and, most incredible of all, his account of the career of Sven Forkbeard. When Adam refers to oral sources, there is every reason to be on the alert.